Rediscovery and revival in Islamic environmental law : back to the future of nature's trust - Idllalene, Samira, 1975- (Cambridge : Cambridge University Press, 2021)
The common ground between religions could be fruitfully promoted in order to call for an effective protection of the climate system. Positioned at a junction of different worlds, this book is a multidisciplinary work on Islamic law, common law and environmental law. Looking at the past, present and future, the author suggests a paradigm shift starting from the common ground in order to propose a better future for environmental law in Muslim countries. As the first book to compare Shari'a and common law in field of environmental protection, it suggests a new path in comparative environmental law by recognizing the contributions of both history and spirituality.
Introductory context and issues -- What is 'Islamic environmental law'? -- The dormancy of Islamic environmental law -- The fruitful comparison with the common law -- Potential for growth of Islamic environmental law.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Environmental law (Islamic law)